Link Adaptive Relaying with Virtual Noise Based Detection in Cooperative Wireless Networks - Bozdag, Ahmet; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2013)
Cooperative communication is an approach that provides diversity gain in wireless communications systems by eliminating the requirement of locating physical antenna arrays at terminals. In this study, a scheme that combines link adaptive relaying (LAR) and virtual noise modeling based detection techniques which have been introduced in the literature to prevent performance degradation in decode and forward based cooperative wireless networks due to error propagation is proposed and its error performance is investigated for Nakagami-m channels. It has been shown by simulation results that the proposed system provides significant performance improvement in various situations with respect to the classcial LAR structures in which maximal ratio combining is employed at the destination.
Keywords: cooperative diversity; error propagation; link adaptive relaying; USER COOPERATION; DIVERSITY; DEMODULATION; Engineering; Telecommunications